2019
DOI: 10.3390/pharmacy7030077
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Reactions and Cross-Reactivity Potential with Beta-Lactamase Inhibitors

Abstract: Although beta-lactam allergies are an emerging focus of stewardship programs and interventions, less is publicly released regarding allergies to beta-lactamase inhibitors. This review presents and evaluates the data regarding allergic reactions with beta-lactamase inhibitors. Clavulanate, sulbactam, and tazobactam are beta-lactam-based beta-lactamase inhibitors that are combined with several penicillins or cephalosporins in order to preserve antimicrobial activity in the presence of beta-lactamases. Avibactam,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…Case reports also document hypersensitivity reactions to the BLI clavulanate (37,38), and one nonimmunological hypersensitivity reaction to tazobactam was previously reported (39,40). However, the latter is not tested separately in our center.…”
Section: Discussionmentioning
confidence: 85%
“…Case reports also document hypersensitivity reactions to the BLI clavulanate (37,38), and one nonimmunological hypersensitivity reaction to tazobactam was previously reported (39,40). However, the latter is not tested separately in our center.…”
Section: Discussionmentioning
confidence: 85%
“…The low rate of cross-reactivity seen between penicillin and carbapenems (<1%), which possess a unique hydroxyethyl side chain, further supports the hypothesis that not only does the R 1 bioisosterism play a dominant role, but aromatic end group chemistry appears causative ( Romano et al, 2006 , 2007 ; Atanaskovic-Markovic et al, 2008 ; Gaeta et al, 2015 ; Buonomo et al, 2016 ). Although not utilized on their own as an antibacterial therapy, β-lactam based β-lactam inhibitors also have been implicated in allergic reactions ( Stover et al, 2019 ). The authors concluded that cross-allergenicity with β-lactams is likely with sulbactam and tazobactam.…”
Section: Resultsmentioning
confidence: 99%
“…In haemato-oncology, professional associations have already developed comprehensive evidence-based guidelines for diagnosis and treatment in certain clinical situations involving infectious diseases, on which a local interdisciplinary ABS programme can be based. Immunosuppressed patients with a history indicating penicillin intolerance (but not clear immediate anaphylactic reactions) must undergo further evaluation to rule out a (very rare) penicillin allergy of the immediate type so as not to be unjustifiably denied the most effective treatment with penicillins or other beta-lactam antibiotics for their indication [ 422 ], [ 423 ], [ 424 ], [ 425 ], [ 426 ], [ 427 ], [ 428 ].…”
Section: Recommendationsmentioning
confidence: 99%